2019
DOI: 10.2147/ijn.s187854
|View full text |Cite
|
Sign up to set email alerts
|

<p>An anti-inflammatory peptide and brain-derived neurotrophic factor-modified hyaluronan-methylcellulose hydrogel promotes nerve regeneration in rats with spinal cord injury</p>

Abstract: BackgroundTraumatic spinal cord injury (SCI) causes neuronal death, demyelination, axonal degeneration, inflammation, glial scar formation, and cystic cavitation resulting in interruption of neural signaling and loss of nerve function. Multifactorial targeted therapy is a promising strategy for SCI.MethodsThe anti-inflammatory peptide KAFAKLAARLYRKALARQLGVAA (KAFAK) and brain-derived neurotrophic factor (BDNF)-modified hyaluronan-methylcellulose (HAMC) hydrogel was designed for minimally invasive, localized, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 47 publications
1
47
0
1
Order By: Relevance
“…Considering the scaffold implantation in this study and meeting the above conditions, the transection model may be an appropriate model for the study of biomaterial scaffolds for SCI repair. In some studies, aneurysm clips were used to establish SCI model, and hydrogel was injected into the injury site after SCI [ 41 ]. The location choice of the injury between T9 and T10 should also be motivated.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the scaffold implantation in this study and meeting the above conditions, the transection model may be an appropriate model for the study of biomaterial scaffolds for SCI repair. In some studies, aneurysm clips were used to establish SCI model, and hydrogel was injected into the injury site after SCI [ 41 ]. The location choice of the injury between T9 and T10 should also be motivated.…”
Section: Discussionmentioning
confidence: 99%
“…An anti-in ammatory combined neuroprotection strategy is one of the most promising options for the treatment of SCI [8,32]. Activation of microglia is one of the earliest in ammatory reactions after injury, and this activation is usually excessive [33].…”
Section: Discussionmentioning
confidence: 99%
“…Yan Sun et al indicated that exercise can ameliorate SCI damage through NF-κB signaling pathways 22. Several studies have also indicated that inhibition of inflammation can improve axonal regeneration 23, 24. In the present study, as the evidence is not clear yet in regards to the direct relationship between congenital exercise ability and inflammation, fibrosis, or demyelination.…”
Section: Discussionmentioning
confidence: 99%